Plasmonics in Analytical Spectroscopy - Aoki, Pedro H. B. [UNESP]; Constantino, Carlos J. L. [UNESP]; Oliveira, Osvaldo N.; Aroca, Ricardo F. [UNESP]; Wang, C.; Leblanc, R. M. (Amer Chemical Soc, 2015)
Surface plasmon resonances (SPR) can be excited in thin metal films and in metal nanoparticles as localized surface plasmon resonances (LSPR). The surface plasmon is extremely sensitive to the refractive index of the environment surrounding the metal film or metal nanoparticle. This is why refractive index sensing has been the source for the development of an array of techniques harnessing the power of both SPR and LSPR. In addition, LSPR is at the center of plasmon enhanced spectroscopy with a myriad of analytical applications. Here we examine the basic physical model of plasmon enhancement, with the intention of facilitating the design of plasmonic nanostructures and experiments, taking advantage of these emerging techniques. In particular, we discuss the plasmon enhanced work based on shell-isolated nanoparticles (SHINs) in Raman scattering (SHINERS) and in fluorescence (SHINEF). Typical examples have been selected to illustrate the physical interpretation of observations.